2014
DOI: 10.1002/anie.201407802
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Formation of Hybrid Peptidic Capsules by Chiral Self‐Sorting and Self‐Assembly

Abstract: Owing to their versatility and biocompatibility, peptide-based self-assembled structures constitute valuable targets for complex functional designs. It is now shown that artificial capsules based on β-barrel binding motifs can be obtained by means of dynamic covalent chemistry (DCC) and self-assembly. Short peptides (up to tetrapeptides) are reversibly attached to resorcinarene scaffolds. Peptidic capsules are thus selectively formed in either a heterochiral or a homochiral way by simultaneous and spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…17 However, to the best of our knowledge, only two studies have been recently reported on intramolecular self-sorting, which involved dynamic covalent chemistry in the syntheses of various peptido-cavitands. 18,19 Carboxamidocavitands, obtained usually by the acylation of the corresponding aminocavitands, 20,21 have strong tendency to form self-assembled dimeric capsules via intermolecular hydrogen bonds. 22 In …”
Section: Introductionmentioning
confidence: 99%
“…17 However, to the best of our knowledge, only two studies have been recently reported on intramolecular self-sorting, which involved dynamic covalent chemistry in the syntheses of various peptido-cavitands. 18,19 Carboxamidocavitands, obtained usually by the acylation of the corresponding aminocavitands, 20,21 have strong tendency to form self-assembled dimeric capsules via intermolecular hydrogen bonds. 22 In …”
Section: Introductionmentioning
confidence: 99%
“…8,9 The tautomerization proceeds in a highly regioselective manner, i.e. [8][9][10] For aliphatic chiral amines two inherently chiral M and P diastereoisomers were clearly visible in NMR spectra and chemical exchange between them was slow on the NMR timescale (EXSY, no exchange detected using a mixing time of 1.5 s). [8][9][10] For aliphatic chiral amines two inherently chiral M and P diastereoisomers were clearly visible in NMR spectra and chemical exchange between them was slow on the NMR timescale (EXSY, no exchange detected using a mixing time of 1.5 s).…”
mentioning
confidence: 99%
“…[8][9][10] For aliphatic chiral amines two inherently chiral M and P diastereoisomers were clearly visible in NMR spectra and chemical exchange between them was slow on the NMR timescale (EXSY, no exchange detected using a mixing time of 1.5 s). 9 For example, (S)-2a exists as a concave monomer in a homochiral form; however, ‡ HJ performed all synthetic work, NMR, CD data interpretation and ab initio calculations. 4 95%).…”
mentioning
confidence: 99%
See 2 more Smart Citations